Translating the realities of a German fairy tale as a means of improving translation competence (Educational Dimension, 2024)
The article deals with the work with the text of a German fairy tale as a means of improving translation competence, a set of exercises and tasks related to the translation of reality with linguistic and cultural specificity from German into Ukrainian and Russian, the concept of reality and its characteristics are defined, the classifications of realities by structural and thematic component are presented. The study identifies the peculiarities of using translation methods of reality with linguistic and cultural specificity based on folk and literary German fairy tales. The importance and complexity of achieving equivalence and adequacy in the process of translation of realities are substantiated. The difficulties in translating realities are identified because realities belong to the group of culture-specific vocabulary with no direct analogues in the target language and are directly related to the specific cultural phenomena of a particular people. The realities with linguistic and cultural specificity found in German fairy tales have been identified and analysed. A comparative analysis of the ways of translating realities with language and cultural specificity has been carried out, and it has been determined that the most widespread ways of translation are generic matching, calibration, functional analogy, and transcription. The study results are summarised, and the prospects for further research are outlined.
Keywords: reality; reality with linguocultural specificity; culture-specific vocabulary; methods of translation; folktale; literary tale; linguocultural specificity; translation competence